Rosyjscy oświeceni wobec (nie tylko) kultury agrarnej (Andriej Bołotow i czasopismo „Sielskij Żytel”) - Dąbrowska, Magdalena (Studia Rossica Posnaniensia, 2019)
The article presents the periodical “Selsky zhitel” (“The Villager”), which was published by Andrey Bolotov in Moscow in 1778–1779. It was the first Russian private agricultural journal with its purpose, programme, structure and contents. Bolotov’s activity and the history of the Russian agricultural journals in the 18th and early 19th century constitute an interpretive background.